2006
DOI: 10.1109/tit.2006.874516
|View full text |Cite
|
Sign up to set email alerts
|

Randomized gossip algorithms

Abstract: Abstract-Motivated by applications to sensor, peer-to-peer, and ad hoc networks, we study distributed algorithms, also known as gossip algorithms, for exchanging information and for computing in an arbitrarily connected network of nodes. The topology of such networks changes continuously as new nodes join and old nodes leave the network. Algorithms for such networks need to be robust against changes in topology. Additionally, nodes in sensor networks operate under limited computational, communication, and ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
2,291
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,081 publications
(2,309 citation statements)
references
References 47 publications
17
2,291
0
1
Order By: Relevance
“…Throughout this paper when we refer to a random geometric graph, we mean one with the connectivity r con (n). Boyd, Ghosh, Prabhakar, and Shah [3] studied scaling laws for pairwise randomized gossip on random geometric graphs and found that communication cost scales as Θ( n 2 log n log −1 ) messages even if the algorithm is optimized with respect to the topology.…”
Section: Previous Work and Known Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout this paper when we refer to a random geometric graph, we mean one with the connectivity r con (n). Boyd, Ghosh, Prabhakar, and Shah [3] studied scaling laws for pairwise randomized gossip on random geometric graphs and found that communication cost scales as Θ( n 2 log n log −1 ) messages even if the algorithm is optimized with respect to the topology.…”
Section: Previous Work and Known Resultsmentioning
confidence: 99%
“…As explained in [3] this facilitates the analysis of gossip algorithms but does not force the actual implementation to be sequential. Multiple communication events happen in parallel.…”
Section: Network Model and Problem Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A convenient way when dealing with agreement in unreliable networks is to exchange messages by an asynchronous framework. The best known one is gossip-based algorithms which have attracted considerable recent attention [5]- [10]. In addition, limitations on the sensor cost, bandwidth, and energy budget dictate that information transmitted between sensors has to be quantized in practice [11]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since each sensor independently processes its own particles, we need to fuse the sensors' information. To achieve distributed information fusion, a consensus algorithm [4] and a gossip method [14,15] are adopted. The consensus algorithm is synchronous, that is, all sensors activate and communicate with their neighbors at each iteration.…”
Section: Introductionmentioning
confidence: 99%